Obesity and endocrine dysfunction in mice with deletions of both neuropeptide Y and galanin - Wynick, D.; Weinshenker, David; Steiner, Robert A.; Clifton, Donald K.; Hohmann, John G.; Teklemichael, Dawit N. (American Society for Microbiology, 2004)
Neuropeptide Y (NPY) and galanin have both been implicated in the regulation of body weight, yet mice bearing deletions of either of these molecules have unremarkable metabolic phenotypes. To investigate whether galanin and NPY might compensate for one another, we produced mutants lacking both neuropeptides (GAL(-/-)/NPY(-/-)). We found that male GAL(-/-)/NPY(-/-) mice ate significantly more and were much heavier (30%) than wild-type (WT) controls. GAL(-/-)/NPY(-/-) mice responded to a high-fat diet by gaining more weight than WT mice gain, and they were unable to regulate their weight normally after a change in diet. GAL(-/-)/NPY(-/-) mice had elevated levels of leptin, insulin, and glucose, and they lost more weight than WT mice during chronic leptin treatment. Galanin mRNA was increased in the hypothalamus of NPY(-/-) mice, providing evidence of compensatory regulation in single mutants. The disruption of energy balance observed in GAL(-/-)/NPY(-/-) double knockouts is not found in the phenotype of single knockouts of either molecule. The unexpected obesity phenotype may result from the dysregulation of the leptin and insulin systems that normally keep body weight within the homeostatic range.
Keywords: neuropeptide Y; galanin; body weight; mice; Neuropeptide Y, genetics, metabolism; Body Weight; Eating; Dietary Fats; Mice, Inbred Strains; Galanin, genetics, metabolism; Endocrine System, physiopathology; Mice, Knockout; Hormones, blood; Dorsomedial Hypothalamic Nucleus, cytology, metabolism; Mice; Circadian Rhythm; Insulin, metabolism; Leptin, administration & dosage, metabolism; Animals; Motor Activity, physiology; Obesity, genetics, metabolism; Research Support, U.S. Gov't, P.H.S.; Phenotype; Research Support, Non-U.S. Gov't; Research Support, U.S. Gov't, Non-P.H.S.; Male